OPTIMASI FORMULA DAN UJI PENETRASI SECARA IN VITRO SEDIAAN GEL HIDROLISAT MEMBRAN CANGKANG TELUR - Rohadatul'aisy, Rifdah
Eggshell membrane (ESM) is an egg component that contains hyaluronic acid, collagen, keratin, and elastin. These components help hydration and improve elasticity of the skin, therefore it can be used as a potential raw material in the development of anti-aging cosmetics. In this research ESM was hydrolyzed enzymatically using a combination of papain and sodium sulfite (Na2SO3). The optimization of hydrolysis time and composition showed a significant effect (p<0,05) on the degree of hydrolysis and the total protein content obtained. The optimum hydrolysis occurred at 6 hours incubation with concentration of papain 0,60%, sodium sulfite 0,32%, and ESM 4% resulted in 76,79±0,76% degree of hydrolysis, total protein concentration 1,22±0,05mg/ml, and 3,73±0,63% hyaluronic acid. The results of in vitro test on collagenase inhibition showed that ESM hydrolysate inhibited collagenase at 45,88±4,18% to 69,59±0,63%, which was not different compared to the inhibition activity of positive control, Epigallocatechin-3-Gallate. ESM hydrolysate was formulated in the form of a gel with optimation of propylene glycol (0-15%) and glycerin (0-7%). The result of ESM hydrolysate in vitro penetration test using Franz diffusion cell showed that the concentration of propylene glycol and glycerin in the hydrolyzed MCT gel preparation was significantly increase hyaluronic acid penetration through skin (p<0.05).